127k views
3 votes
Can someone tell me the answers and show how you did it step by step with the parentheses and everything?

Can someone tell me the answers and show how you did it step by step with the parentheses-example-1

2 Answers

2 votes

Answer:

Solution : - 20

Explanation:

We have the following expression to simplify,


\left\{\left[(\left(3+5\right))/(2)\right]^2-\left(3\cdot 2\right)\right\}\cdot \left(-2\right)

Let's start by simplifying simple expressions, such as 3 + 5 = 8 and 3 * 2 = 6. Substituting we receive,


\left\{\left[(\left(8\right))/(2)\right]^2-\left(6\right)\right\}\cdot \left(-2\right)

8 / 2 = 4, and 4² = 16 -


\left\{16-\left(6\right)\right\}\cdot \left(-2\right)

And of course 16 - 6 = 10, simplifying the expression to " - 2
* 10 " leaving us with a solution of - 20.

User L Xandor
by
5.5k points
3 votes

Explanation:

Following B. O. D. M. A. S rule :

= { [ 8 / 2] ^2 - 6} * (-2)

= { 4 ^ 2 - 6} * - 2

= 10 * - 2

= - 20

User Michael McCabe
by
4.2k points